Juridical analysis of legal certainty and protection of the parties in the cooperation agreement for the establishment of a health clinic at PT. Melaka Medives Cakra, Batam City - Dedy Cakra Wijaya; H.M. Soerya Respationo; Erniyanti Erniyanti (Annals of Justice and Humanity, 2025)
Purpose: This study aims to analyze the legal arrangements, implementation, as well as obstacles and solutions in cooperation agreements for the establishment of health clinics at PT Melaka Medives Cakra in Batam City. The focus lies on aspects of legal certainty and the protection of parties involved. The research uses a combination of normative juridical and empirical juridical approaches. Method: Data were collected through the study of laws and regulations, legal literature, and primary sources, including interviews with stakeholders and field observations. The analysis is based on positive law theory, Lawrence M. Friedman’s legal system theory, and Sudikno Mertokusumo’s legal certainty theory. Result: Although the cooperation agreement was legally valid as an authentic deed, issues such as vague clauses, differing interpretations, and administrative barriers arose. Through addenda, legal support, and stronger dispute resolution clauses, the parties maintained stability and ensured fair legal protection. Conclusion: The study concludes that clarity in contract drafting, early involvement of legal assistance, and simplified licensing procedures are crucial for ensuring legal certainty and sustainable cooperation in the health care sector. Limitation: This research is limited to a single case study in Batam City, thus its findings may not fully represent similar cooperation agreements in other regions or health sectors. Contribution: The study contributes by providing practical insights into strengthening legal certainty in health sector cooperation agreements. It offers recommendations for policymakers, practitioners, and stakeholders to foster a legal ecosystem that supports sustainable collaboration and equitable protection of rights.